Hb Rush (HBB: c.304G>C): A Rare Variant Hemoglobin Mimicking the Hb S (HBB: c.20A>T) Variant on High Performance Liquid Chromatography. (2nd January 2020) - Mashon, Ranjeet S.; Das, Reena; Dhawan, Radhika; Kakkar, Naveen; Dhar, Tapasya
Abstract: High performance liquid chromatography (HPLC) is a useful and rapid tool in the evaluation of hemoglobin (Hb) disorders that include thalassemia and various hemoglobinopathies. Most of the techniques or programs used in automated testing platforms are customized to identify the common variants seen in that particular region. At times, variant Hbs may be identified which are not commonly seen in the local population. This may cause diagnostic dilemma and may require further studies for definitive characterization. We present a patient with Hb Rush ( HBB : c.304G>C), a rare unstable Hb variant eluting in the Hb S ( HBB : c.20A>T) window on HPLC.